Bulk and interfacial properties of milk fat emulsions stabilized by whey protein isolate and whey protein aggregates. (December 2020) - Zhou, Xilong; Sala, Guido; Sagis, Leonard M.C.
Abstract: Whey protein is widely used in the food industry as an emulsion stabilizer because of its outstanding emulsifying ability. Recent studies have shown that heat-induced whey protein aggregates may also have potential to stabilize emulsions. The interfacial behavior of whey protein and whey protein aggregates adsorbed at the milk fat-water interface has not been well investigated, especially not in the nonlinear regime, which is highly relevant for the preparation of products such as recombined dairy cream. In this study, the interfacial properties of milk fat-water interfaces stabilized by whey protein isolate (WPI) and whey protein aggregates (WPA) at different bulk concentrations (0.1 wt% - 4.0 wt%) were studied by Large Amplitude Oscillatory Dilatation (LAOD). Lissajous plots were used to analyse the nonlinear response of the interfaces as a function of strain amplitude and frequency. The elastic modulus was quantified based on the tangent modulus at zero instantaneous strain in expansion and in compression. Bulk stability of creams stabilized with the mentioned proteins was studied by determining creaming rate, droplet size distribution, ζ-potential and viscosity of the continuous phase. At low concentrations (<2.0 wt%), WPI-stabilized cream had smaller oil droplets than WPA-stabilized cream, indicating that at these concentrations WPI had better emulsifying ability. For concentrations higher than 2.0 wt%, WPA was a better emulsifier in terms of creaming stability because of the higher viscosity of the continuous phase of the emulsions. Both WPI and WPA could prevent coalescence equally well if the concentration was higher than 0.5 wt%. LAOD measurements showed that at a protein concentration of 0.1 wt%, there was little difference between WPI- and WPA-stabilized interfaces. At 4.0 wt%, WPI showed abrupt intra-cycle yielding followed by a predominantly viscous behavior at large expansion. The WPA interfacial layer had a larger maximum linear strain, and showed a more gradual softening in expansion and mild strain hardening in compression. We hypothesize that WPI formed denser and more brittle (quasi-) 2d structures at the interface, while the interfaces formed by WPA might have a thicker and more stretchable 3d structure. The WPA-stabilized emulsion was less resistant to coalescence upon drastic stirring, which can be explained with its different large deformation behavior, and is relevant for applications where the cream is subjected to large deformations (whipping or stirring). Graphical abstract: Image 1 Highlights: WPA is a better emulsion stabilizer than WPI at high concentration. This results from the thickening effect of WPA. WPI appears to form denser and more brittle (quasi) 2d structures at the interface. WPA seems to form thicker 3d structures after adsorption. WPI provides better bulk stability for emulsions at dynamic conditions than WPA.